L-lactic acid and sodium p-toluenesulfonate co-doped polypyrrole for high performance cathode in sodium ion battery. (April 2018) - Liao, Qishu; Hou, Hongying; Liu, Xianxi; Yao, Yuan; Dai, Zhipeng; Yu, Chengyi; Li, Dongdong
Abstract: In this work, polypyrrole (PPy) was co-doped with l -lactic acid (LA) and sodium p -toluenesulfonate (TsONa) for high performance cathode in sodium ion battery (SIB) via facile one-step electropolymerization on Fe foil. The as-synthesized LA/TsONa co-doped PPy cathode was investigated in terms of scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), galvanostatic charge/discharge and cyclic voltammetry (CV). The results suggested that some oval-bud-like LA/TsONa co-doped PPy particles did form and tightly combine with the surface of Fe foil; furthermore, LA/TsONa co-doped PPy cathode also delivered higher electrochemical performances than TsONa mono-doped PPy cathode. For example, the initial specific discharge capacity was as high as about 124 mAh/g, and the reversible specific capacity still maintained at about 110 mAh/g even after 50 cycles, higher than those of TsONa mono-doped PPy cathode. The synergy effect of multi components of LA/TsONa co-doped PPy cathode should be responsible for high electrochemical performances. Highlights: LA/TsONa co-doped PPy was synthesized for high performance cathode in SIB. Co-doped PPy cathode delivered higher electrochemical performances than TsONa/PPy. The underlying electrochemical mechanism was also explored and discussed. The synergy effect may be responsible for high electrochemical performances.